2022
DOI: 10.15294/kemas.v17i4.33365
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Low Birth Weight in Indonesia

Abstract: Low birth weight (LBW) is one of the main factors influencing the development of chronic disease in adulthood in surviving or surviving infants. This study aims to determine the determinants of the incidence of LBW in toddlers (infants aged 0-5 years) in Indonesia. This study uses a data set from the 2017 Indonesian Demographic and Health Survey (IDHS). The dependent variable is the child’s LBW status, while the independent variable consists of 3 variable blocks, namely; distal, intermediate and proximal varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…In this study, a very high incidence of LBW (41%) was observed during the study period (January to December 2019), exceeding the average incidence in Asia (17.3%) (Blencowe et al, 2019; United Nations Children's Fund [UNICEF] and World Health Organization [WHO], 2019). However, the latest incidence reported in Indonesia was 7%, indicating a significant reduction from that previously reported (Oktriyanto et al, 2022).…”
Section: Resultsmentioning
confidence: 58%
“…In this study, a very high incidence of LBW (41%) was observed during the study period (January to December 2019), exceeding the average incidence in Asia (17.3%) (Blencowe et al, 2019; United Nations Children's Fund [UNICEF] and World Health Organization [WHO], 2019). However, the latest incidence reported in Indonesia was 7%, indicating a significant reduction from that previously reported (Oktriyanto et al, 2022).…”
Section: Resultsmentioning
confidence: 58%
“…LBW is the main cause of death in children in Indonesia (Oktriyanto et al, 2022). LBW babies generally have a greater risk of morbidity and death compared to babies with normal weight.…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian yang dilakukan oleh Safitri dkk menyatakan bahwa faktor-faktor yang berkaitan dengan BBLR yaitu jumlah kunjungan Antenatal Care (ANC) dan tingkat pendidikan ibu (6). Penelitian lain yang dilakukan oleh Oktriyanto dkk menyatakan bahwa faktor yang mempengaruhi terjadinya BBLR yaitu anak yang lahir kembar, ibu tidak mengonsumsi tablet besi selama hamil, dan pendapatan keluarga yang rendah (7). Adapun Wang menyatakan bahwa usia ibu saat hamil meningkatkan risiko BBLR.…”
unclassified